Independent value of left atrial volume index for the prediction of mortality in patients with suspected heart failure referred from the community. Issue 14 (8th April 2009) - Lim, T K; Dwivedi, G; Hayat, S; Majumdar, S; Senior, R
Abstract : Background: The left atrial volume index (LAVI) reflects left ventricular (LV) filling pressure and has been shown to predict outcome in various cardiovascular diseases. However, its value for the prediction of mortality in patients referred for suspected heart failure (HF) is unknown. Objective: To assess the value of LAVI for the prediction of mortality independently of clinical, electrocardiographic (ECG) and echocardiographic prognostic parameters in patients with suspected HF referred from the community. Methods: 356 (mean (SD) age 72 (13) years) patients with suspected HF referred from the community were followed up for mortality after undergoing clinical assessment, ECG and echocardiography, including Doppler, to assess LV filling. Results: Data were obtained for 335/356 (94%) patients (162 male, 173 female) over a mean (SD) follow-up period of 30 (10) months, during which 38 (11.3%) died. The univariate predictors for all-cause mortality were age, symptom of leg swelling, clinical signs of HF, abnormal ECG, LV ejection fraction, LAVI, LV end-systolic (LVESD) and diastolic dimension, septal wall thickness and the presence of other significant cardiac abnormalities. The only independent predictors of mortality were age (hazard ratio (HR) = 2.15, 95% CI 1.42 to 3.25, p<0.001), symptom of leg swelling (HR = 2.83, 95% CI 1.43 to 5.59, p = 0.005), LAVI (HR = 1.25, 95% CI 1.01 to 1.54, p = 0.04) and LVESD (HR = 1.32, 95% CI 1.02 to 1.70, p = 0.04). Conclusion: LAVI provided independent information over clinical and other echocardiographic variables for predicting mortality in patients with suspected HF referred from the community.